Aplicação de Análise Multivariada de Dados na Identificação de Espécies de Cyperaceae Típicas da Região Amazônica. - Vilhena, Karyme S. S. (Museu Paraense Emilio Goeldi, 2018)
The present work deals with the subject of the essential oils obtained from the species Cyperus articulatus var. articulatus and C. articulatus var. nodosus, commonly known by the name of priprioca widely used by the domestic industry in the production of perfumes.